Optimization of the Cremator Settings for the Disposal of Poultry Waste By Incineration in a Beet-emitting Boiler - Konovalov, Victor; Konovalova, Anna; Konovalov, Vladimir; Denisov, Sergey; Gumarov, Gali (KnE Life Sciences, 2020)
The purpose of this work is to substantiate the parameters of the boiler unit, which ensures the cremation of manure using microwave radiation. The substantiation of the amount of heat released during the burning of chicken manure at the industrial keeping of poultry in the conditions of sharply continental climate on the basis of minimization of product utilization values - ash content of wastes and pollution of smoke emissions is presented. Using the obtained regression models of magnetron emission power, moisture content of the burnt manure mass, mass air consumption for the specified product utilization parameters, the analysis of the relationship between the obtained parameters is made. Correlation analysis has shown a high correlation between the amount of heat released during the combustion of manure and the concentration of carbon monoxide in the smoke emissions. Rationally, the value of carbon monoxide content in the flue gases is 3.9%, corresponding to the amount of heat released 2.1 MJ/kg at the combustion of a kilogram of manure at the ash content of the residue of 18.4% and the initial moisture content of the manure of 38.4%. It provides power of radiation of magnetron 400 W on 1 kg of a waste and the mass flow rate of air of 13.8 kg/h.